2020
DOI: 10.1080/13632752.2020.1771923
|View full text |Cite
|
Sign up to set email alerts
|

Towards a dynamic interactive model of resilience (DIMoR) for education and learning contexts

Abstract: and Hatley, Jenny (2020) Towards a dynamic interactive model of resilience (DIMoR) for education and learning contexts. Emotional and Behavioural Difficulties, 25 (2). pp. 183-198.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Despite a growing interest in either resiliency-trait or resilience-state research across various contexts and fields of psychology, there is still no commonly accepted definition of resiliency/e. This is evident in a plethora of concept analyses (including theoretical, empirical, contextual, and interdisciplinary reviews) spanning the last two decades (see Aburn et al, 2016; Ahern et al, 2008; Ahmed Shafi et al, 2020; Atkinson et al, 2009; Bonanno et al, 2015; Lou et al, 2018; Luthar et al, 2000; Pooley & Cohen, 2010; Sanderson & Brewer, 2017; Schultze-Lutter et al, 2016; Southwick et al, 2014; Windle, 2011; Zolkoski & Bullock, 2012). As Aburn et al (2016) concluded: “The most significant finding of the review was that there is no universal definition of resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a growing interest in either resiliency-trait or resilience-state research across various contexts and fields of psychology, there is still no commonly accepted definition of resiliency/e. This is evident in a plethora of concept analyses (including theoretical, empirical, contextual, and interdisciplinary reviews) spanning the last two decades (see Aburn et al, 2016; Ahern et al, 2008; Ahmed Shafi et al, 2020; Atkinson et al, 2009; Bonanno et al, 2015; Lou et al, 2018; Luthar et al, 2000; Pooley & Cohen, 2010; Sanderson & Brewer, 2017; Schultze-Lutter et al, 2016; Southwick et al, 2014; Windle, 2011; Zolkoski & Bullock, 2012). As Aburn et al (2016) concluded: “The most significant finding of the review was that there is no universal definition of resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting on the data through the lens of the DIMoR leads to key reminders about the nature of resilience. Our findings demonstrate that resilience is not a static, in-person trait but something that changes as a result of circumstances and reactions to those circumstances (ahmed Shafi et al, 2020). Consequently, it is important to be mindful that we should not take resilience for granted and recognise that individuals who appear to be resilient in certain contexts may not be in others as circumstances change.…”
Section: What Does the Dimor Tell Us About Resilience Of University S...mentioning
confidence: 76%
“…Support for this adaptive capacity can originate within individuals, from their more proximal contexts of family and institutions of which they are part or from more distal influences such as government and policy. The Dynamic Interactive Model of Resilience (DIMoR) proposed by ahmed Shafi et al (2020), where resilience is recognised as an adaptive capacity within a scaled systems context, provides a useful lens through which to view, analyse and interpret the resilience of systems (Figure 1). As Figure 1 demonstrates, the adaptations that universities and their staff had to make as a result of the pandemic can be considered protective or risk factors for the individual (or the system in which the individual is situated), influencing their vulnerabilities and invulnerabilities (ahmed Shafi et al, 2020).…”
Section: Role Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…However, the systemic view of resilience calls into question many of the assumptions that underpin such interpretations. Interactive models emphasise reciprocal effects, for example between individual agency and the wider social system (Ahmed Shafi, 2020). Such approaches highlight the need to explore how person-situation (internal-external) influences interact to shape the way resilience changes over time, and the importance of factoring both in when designing any intervention to strengthen people’s resilience.…”
Section: Introductionmentioning
confidence: 99%